Ekstrakurikuler Tari Persembahan di SMK Negeri 1 Kuok T.A 2023/2024 - Delfi Rahmi; Yahyar Erawati (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2024)
This research aims to find out the extracurricular dance offerings at SMK Negeri 1 Kuok T.A 2023/2024. The research method used in this research is descriptive analysis, with a qualitative approach, the reason the author took this research is because this method involves directly the object being studied. The subjects in this research were 15 people, the location of this research was carried out at SMK Negeri 1 Kuok, which is on Jalan Sei Maki, Kuok sub-district, Kampar district. From the results of the analysis of findings in the field, the conclusion was drawn that the material taught in Persembahan dance. The method used in the dance extracurricular at SMK Negeri 1 Kuok was the lecture and practice method. The data collection techniques used in this research are observation, interview and documentation data collection techniques. Extracurricular dance facilities and infrastructure include an arts room for practice, laptops, speakers and cellphones.